2013
DOI: 10.1155/2013/213234
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Trabecular and Cortical Bone Microstructure

Abstract: The elderly population has substantially increased worldwide. Aging is a complex process, and the effects of aging are myriad and insidious, leading to progressive deterioration of various organs, including the skeleton. Age-related bone loss and resultant osteoporosis in the elderly population increase the risk for fractures and morbidity. Osteoporosis is one of the most common conditions associated with aging, and age is an independent risk factor for osteoporotic fractures. With the development of noninvasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
166
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(197 citation statements)
references
References 56 publications
(109 reference statements)
14
166
3
7
Order By: Relevance
“…Similar results were obtained in several previous studies. (13,17,18) However, the percentage of subjects with low BMD in the present study was relatively high as compared with the aforementioned studies, and even with a previous study in Indonesia. (3) The difference may be the result of differences in T score cut off values, subject characteristics, type of DXA equipment and their operators.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Similar results were obtained in several previous studies. (13,17,18) However, the percentage of subjects with low BMD in the present study was relatively high as compared with the aforementioned studies, and even with a previous study in Indonesia. (3) The difference may be the result of differences in T score cut off values, subject characteristics, type of DXA equipment and their operators.…”
Section: Discussioncontrasting
confidence: 61%
“…The OST sensitivity was highest for BMD of the proximal femur or total hip because in these regions the cortical bone thinned out more rapidly as a result of aging and underwent fractures. (18) The number of subjects with low BMD in the present study was substantial. According to bone location, low BMD was most frequent in the lumbar spine.…”
Section: Discussionmentioning
confidence: 61%
“…These results suggested that ASC treatment protected not only periarticular but also systemic bone loss. Trabecular bone remodeling (turnover) units occur in much greater numbers due to high surface area/bone matrix volume configuration than the cortical bone, resulting in bone turnover rate at the trabecular sites being much higher than at the cortical sites (39). Therefore, increased osteoclastogenesis under any pathological condition such as the one we observed with CIA is more likely to result in the loss of trabecular bones over cortical bones as the remodeling event is triggered by osteoclasts.…”
Section: Discussionmentioning
confidence: 81%
“…Bone strength, estimated using micro-finite element analysis (μFEA), was also associated with prevalent fracture [6][7][8][9][10][11][12][13][14]. Moreover, HR-pQCT has been used to assess age-related bone loss [15][16][17][18][19] and to monitor variations in microarchitecture parameters during osteoporosis treatments [20][21][22][23][24][25][26].…”
Section: T R a C T A R T I C L E I N F O Introductionmentioning
confidence: 99%